Effects of dietary supplementation with different amounts of Lycium ruthenicum (black goji berry) branch roughage on plasma biochemical indices and rumen microflora of sheep - Hou, Liangzhong; Ma, Yan; Li, Jinlong; Yang, Yuxia; Duan, Pingping; Guo, Tongjun (Frontiers in Microbiology, 2025)
This study aimed to evaluate the effects of dietary supplementation with roughage derived from black goji berry (Lycium ruthenicum) branches on plasma biochemical indices, and rumen microbiota in sheep. Forty male F1 lambs of Dupo×Hu sheep crossbreeds, approximately 4 months of age with similar body weight (29.58 ± 2.06 kg) and in good health, were selected and randomly divided into four groups (n = 10 per group). The control group was fed a full-mixed pelleted ration, and the experimental groups received the same diet supplemented with 10% (H1), 20% (H2) or 30% (H3) L. ruthenicum branch roughage. The addition of different amounts of L. ruthenicum roughage to the feed significantly increased the apparent digestibility of neutral detergent fiber, and antioxidant and immune indices of the sheep without negative effects on liver function. Additionally, the relative abundance of the gut bacteria NK4A214_group in the Oscillospiraceae family increased linearly and quadratically with the amount of L. ruthenicum roughage added to the diets. This findings suggest that bioactive components (e.g., flavonoids, terpenoids, organic acids) in L. ruthenicum branches may strengthen nutrient digestibility and immune performance by altering the type and abundance of rumen microbiota associated with fiber digestion and immunoregulation. Addition of 20–30% L. ruthenicum branch roughage to sheep fodder remarkably improved the growth performance and overall health.